ANALISIS PROGRAM PENGEMBANGAN PROFESI GURU PADA MATA PELAJARAN MATEMATIKA DALAM MENINGKATKAN MUTU LULUSAN SISWA SDI MAMBAUL ULUM PANJUNAN WARU SIDOARJO - Jundhana, Aizza; Muhammad Yusron Maulana El-Yunusi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the teacher professional development program in mathematics at SDI Mambaul Ulum Panjun Waru Sidoarjo and its impact on student graduation quality. In an evolving educational context, the quality of teaching by educators is a key factor in achieving optimal learning outcomes. A qualitative research method was employed, involving interviews with teachers, classroom observations, and analysis of documents related to the professional development program. The findings indicate that the professional development program, which includes training, seminars, and collaborative sessions among teachers, has had a significant positive impact. Teachers involved in this program demonstrated enhanced understanding of mathematical concepts and innovative teaching methods. Students taught by these participating teachers exhibited better learning outcomes, evidenced by improved grades and a deeper comprehension of mathematical material. Additionally, the program fostered the creation of a learning community among teachers, contributing to the exchange of ideas and best practices in teaching. These findings underscore the importance of sustained support for teacher professional development as a long-term investment in education. Consequently, this study recommends that school authorities and other stakeholders continue to develop and strengthen teacher professional development programs to enhance educational quality and produce more competent graduates prepared to face future challenges. Keywords: Professional development, teacher, mathematics, student quality, elementary education.